Transoral micro-endoscopic KTP-532 Laser-assisted excision of hypopharyngeal cancers: Our experience - Dipak Ranjan Nayak; Suraj Nair; Ramaswamy Balakrishnan; Apoorva Reddy (Journal of Head & Neck Physicians and Surgeons, 2016)
Aim: To evaluate the overall and disease specific survival rate in patients with hypopharyngeal cancers treated with KTP - 532 LASER. Materials and Methods: We present a retrospective observational study conducted between January 2000 and December 2012 on a total of 28 patients of biopsy-proven cases of squamous cell carcinoma of hypopharynx in Stages I-IV including eight radio-residual cases who underwent trans-oral micro-endoscopic KTP-532 laser-assisted excision of the primary lesion. All patients with clinically and radiologically positive N status underwent modified neck dissection within 10 days. Average follow-up period was 15 months. All the cases received adjuvant radiotherapy except for the radio-residual ones which were managed with salvage surgery alone. Observation and Results: 25/ 28 patients had no disease on their last follow-up with 3 locoregional recurrences. Nineteen patients were followed up for 2 years or more and we found two loco-regional recurrences within 2 years. Overall survival rate was found to be 89.2% and 2-year specific disease-free survival rate 89.4% as calculated using Kaplan-Meier scale. Conclusion: This study evaluates the efficacy and survival rate of patients who underwent trans-oral micro-endoscopic KTP-532 laser-assisted excision for hypopharyngealcancers in various stages as an alternative to conventional open surgeries.